Significance of Myocytes With Positive DNA In Situ Nick End-Labeling (TUNEL) in Hearts With Dilated Cardiomyopathy - Motoo Kanoh; Genzou Takemura; Jun Misao; Yukihiro Hayakawa; Takuma Aoyama; Kazuhiko Nishigaki; Toshiyuki Noda; Takako Fujiwara; Kazunori Fukuda; Shinya Minatoguchi; Hisayoshi Fujiwara (1999)
Background —The presence of apoptotic myocytes has been reported in human hearts with dilated cardiomyopathy (DCM) on the basis of a positive finding of DNA in situ nick end-labeling (TUNEL). However, ultrastructural evidence of myocyte apoptosis has not been obtained. Methods and Results —A total of 80 endomyocardial biopsies were obtained from right and left ventricles of 20 patients with DCM and 20 normal control subjects. TUNEL-positive myocytes were found by light microscope in 15% of DCM specimens (controls, 0%, P <0.05), and the percentage of TUNEL-positive myocytes per section in DCM was 1.0±2.7% (mean±SD). According to TUNEL at the electron microscopic level (EM-TUNEL), immunogold particles, which label DNA breaks with 3′-OH terminals, were markedly accumulated in the bizarre-shaped nuclei, with widespread clumping of chromatin (so-called “hypertrophied nuclei”) of the myocytes obtained from DCM. Their ultrastructure was neither apoptotic nor necrotic but rather that of living cells. Taq polymerase–based DNA in situ ligation assay, which detects double-stranded DNA fragments more specifically than TUNEL, did not detect a positive reaction in any case. In mirror sections, all of the TUNEL-positive myocytes in DCM simultaneously expressed proliferating cell nuclear antigen, which is required for both DNA replication and repair, but Ki-67, a replication-associated antigen, was completely negative in all cases, which appeared to rule out cell proliferation activity. Conclusions —Most of the TUNEL-positive myocytes in hearts with DCM are not apoptotic but rather living cells with increasing activity of DNA repair.